The ecological sustainability of potato production in the sandveld region of the Western Cape: nutrient and water use efficiencies - Kayes, Malcolm Jeremy (Stellenbosch : Stellenbosch University, 2019)
Thesis (MScAgric)--Stellenbosch University, 2019.